Kung Fu panda 3-movie collection. [videorecording (DVD)] - Jolie, Angelina, 1975- actor (Twentieth Century Fox Home Entertainment LLC., 2018)
"In Kung Fu Panda, a fun-loving panda named Po embraces his destiny as the Dragon Warrios. Then in Kung Fu Panda 2, Po and his fellow kung fu masters band together to protect the Valley of Peace from a fierce rival. And in Kung Fu Panda 3, Po must train an entire village of clumsy pandas to defeat an ancient villain!"--Container